2020
DOI: 10.37290/ijpp2641-7197.15:7-21
|View full text |Cite
|
Sign up to set email alerts
|

Use of Probiotics in Commercially Important Finfish Aquaculture

Abstract: Finfish aquaculture is one of the quickly developing food industries in the world. But, the major drawbacks of this industry are the frequent outbreak of infectious diseases due to elevated stress in an intensive culture system. Antibiotics are extensively used to combat these diseases. Prophylactic administrations of antibiotics in aquaculture lead to the emergence and spread of antibiotic-resistant pathogens which indirectly cause a risk to health of human. Therefore, hard rules and regulations have been est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Previous researches have shown that probiotics improved the survival rates of sh to pathogenic Aeromonas hydrophila, Flavobacterium psychrophilum, Streptococcus iniae, Vibrio harveyi, and Pseudomonas uorescens [39][40][41] are some of the strains that have been identi ed. The survival rates of the treated red hybrid tilapia with free or varied concentrations of probiotic cells (17-63%) were higher than those of the infected sh that were not treated with probiotics (CON + ) (4%).…”
Section: Anti-pathogenicity Against Streptococcus Agalactiae and Histopathological Assaymentioning
confidence: 99%
“…Previous researches have shown that probiotics improved the survival rates of sh to pathogenic Aeromonas hydrophila, Flavobacterium psychrophilum, Streptococcus iniae, Vibrio harveyi, and Pseudomonas uorescens [39][40][41] are some of the strains that have been identi ed. The survival rates of the treated red hybrid tilapia with free or varied concentrations of probiotic cells (17-63%) were higher than those of the infected sh that were not treated with probiotics (CON + ) (4%).…”
Section: Anti-pathogenicity Against Streptococcus Agalactiae and Histopathological Assaymentioning
confidence: 99%
“…Because of good nutritional quality, the dried biofloc is proposed as an ingredient to replace the fishmeal or soybean partially in the feed for aquaculture; but the availability and diversity of dried biofloc are limited. Moreover, biofloc is also a probiotic source and has a probiotic-like beneficial effect in aquaculture production ( Ferreira et al 2015 ; Vikaspedia 2019 ; Jamal et al 2020 ). Altogether, in an integrated system of BFT and RAS, excessive feeds which are used for the rapid growth of cultured animals would be converted more efficiently into microbial biomass, which in turn can be consumed as food by the animals resulting in less pollution of water ( Choo and Caipang 2015 ).…”
Section: Biofloc Is a Significant Food Source In The Recirculating Aqmentioning
confidence: 99%
“…The need of sharing precise knowledge on all relevant subjects is becoming a basic fundamental for aquaculture's responsible management [1]. During the past few years, traditional use of antibiotics in aquaculture has been criticized due to the potential development of antibiotic-resistant bacteria, the presence of antibiotic residues in fish flesh, and the destruction of microbial populations in the culture environment [4]. As an alternative to antibiotics, probiotics have attracted extensive scientific and commercial attention in the aquaculture industry [4].…”
Section: Introductionmentioning
confidence: 99%